The complete Old English poems - Williamson, Craig; Shippey, T. A.; Alfred (The Middle Ages series, 2017)
Includes the Junius manuscript, Exeter book, Vercelli book, Beowulf and Judith, metrical psalms of Paris Psalter and the meters of Boethius, poems of the Anglo-Saxon chronicle, riddles, charms, and a number of minor additional poems
Keywords: Didactic poetry, English (Old); English poetry; Epic poetry, English (Old); Old English, ca. 450-1100; Riddles, English (Old); Translations into English